An investigation into the pedagogy of bridging class teachers within a mainstream school - Isaacson, Ruth Clare (My University, 2016)
This qualitative research aims to explore the constructs of Bridging Classes within a mainstream environment. The investigation focuses primarily on how the teacher works with what Bernstein (1973) considers key aspects to education relay, namely curriculum, pedagogy and assessment. Bridging Classes are provided for learners with moderate learning disabilities that may be caused by an attention deficit disorder or emotional upheaval due to chaotic home circumstances. The deconstruction process is conducted through the lens of Productive Pedagogy which Lingard, Hayes & Mills (2003) developed with four key components, namely, Intellectual Quality, Supportive Classroom Environment, Engagement with Difference, and Connectedness to the World. Productive Pedagogies support sociologists, Bernstein’s (2004) and Bourdieu’s (1999) belief that a universal pedagogy could ensure that learners from all backgrounds can access knowledge. The pedagogy applied in Bridging Class supports this notion by using a high quality curriculum but working at a slower pace, providing opportunities to consolidate concepts and integrating learners back into the mainstream when they are ready. Three teachers from Grade 1, 2, and 3 respectively were asked to participate in this research. The investigation comprised of interviews and observations of Maths and English lessons. The teachers were asked, during interviews, to reflect on their perceptions, experiences and pedagogy as Bridging Class teachers. The research applied a thematic analysis to identify patterns within the data set After coding, themes which emerged were the Cognitive and Academic Challenges Bridging Class learners experience. There are also suggested Strategies for Support to create a learning environment to enhance the academic and social outcomes for Bridging Class learners in a mainstream school. Key Words: Bridging Class, Mainstream, Productive Pedagogy, learning disabilities, perceptions, experience, support, strategies, learning environment.
A Research Report submitted to the Faculty of Education University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Education.
Keywords: Effective teaching--South Africa; Teaching--South Africa--Methodology; Children with mental disabilities--Education--South Africa; Education, Elementary--South Africa